PERCEIVED ORGANIZATIONAL SUPPORT (POS) DAN LEADER-MEMBER EXCHANGE (LMX): PENGARUHNYA TERHADAP - Tri Wikaningrum (Jurnal Bisnis dan Ekonomi, 2007)
This study examined a model of consequences of perceived organizational support (POS) and leader-member exchange (LMX). Employees develop exchange relationships both with organizations and immediate superiors as evidenced by this research. It was predicted that POS and LMX would influence work attitudes and behavior. Results based on a sample of 86 nurses indicated that POS was related to organizational commitment and organizational citizenship behavior (OCB), whereas LMX was related to organizational commitment, job satisfaction, and OCB, that providing support for the importance of both types of exchanges. Keywords : POS, LMX, Organizational Commitment, job satisfaction, OCB.